Coping strategies and barriers to coping in climate- vulnerable Bangladesh: a qualitative study: Kyra Lilier. (25th October 2022) - Lilier, K; Selim, SA; Raihan, ST; Islam, R; Das, J; Danquah, I; Sauerborn, R; Bärnighausen, K
Abstract: : With the mental wellbeing of billions of people at risk due to climate change, more research is required to better understand mental health and psychological implications of climate vulnerability. This research contributes to understanding how people in climate vulnerable populations psychologically cope with stress with crucial implications for adaptation efforts. We conducted n = 60 qualitative in-depth interviews with men and women in Bhola, Bangladesh to elicit the lived experiences of a climate vulnerable population. We analysed data following the tenets of Grounded Theory. Through our inductive analysis, we found coping strategies where participants highlighted what they did when encountering stress, such as 'Resignation' or 'Help Seeking'. Barriers to coping were, among others, limited 'Efficacy', 'Time' or 'Stigma'. We categorized coping strategies with barriers as high-barrier coping strategies and, those without reported barriers, as low- barrier coping strategies. High-barriers restricted participants - especially women - in their coping efforts and led them to using low-barrier coping strategies. Some low-barrier coping strategies can be interpreted as maladaptive if used frequently, as they are unhealthy and draw upon resources needed to adapt for the future. Maladaptive coping strategies can thus impede long-term adaptation by reducing motivation and the ability and willingness to act. To enable adaptive coping, we recommend lifting the barriers to coping through community-led interventions where community workers create platforms for sharing problems and knowledge, such as group support meetings. Sharing and discussing could strengthen efficacy and open new opportunities for functional, adaptive coping. As the negative impacts of climate change will be felt globally with more intensity and frequency, enabling adaptive coping and removing barriers to coping in frontline communities will be essential to supporting physical and mental wellbeing. Key messages: Barriers to adaptive coping strategies can lead people to using maladaptive low-barrier coping strategies, which draw upon resources needed for long-term adaptation. Enabling adaptive coping by lifting barriers to coping in climate vulnerable populations is crucial to strengthen adaptation efforts.